Transferred, mediated or transformed: considering the design, features, and presentation of sacred text mobile applications - Tsuria, Ruth (Journal of contemporary religion, 2021)
This comparative study of 100 iTunes mobile applications featuring sacred texts from five major world religions emphasizes how such texts are represented when digitized. Specifically, this research investigates the technological affordances these apps offer, how these affordances are communicated to users, and the messages about religion these app designs communicate. This article thus portrays the relationship between innovative technological features and traditional religious presentations of sacred texts in mobile apps. We find that app designers use one of three strategies so that sacred texts become either transferred, mediated or transformed when digitized.